β-glucuronidase activity determination as an indirect estimate of Escherichia coli: development of a miniaturized assay and its application to seawater samples - Caruso G; Caruso R; Monticelli LS; Maimone G; Crisafi E (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2017)
Background: The search of rapid methods for the detection of Escherichia coli in coastal marine waters is a topic of scientific interest to evaluate potential risks to human health related to their low bacteriological quality.  The context and purpose of the study: A miniaturized assay for the analytical determination of β−glucuronidase activity in seawater as a selective marker of Escherichia coli was developed by using the chromogenic Indoxyl-β-D-glucuronide (IBDG) substrate. This compound is specifically cleaved by E. coli, releasing an insoluble chromophoric blue-indigo product that precipitates and is measured at 450 nm wavelength by a microplate reader. Results: After its preliminary optimization, the enzymatic assay was applied to the analysis of seawater samples and enabled to discriminate them according to their pollution level.  Main findings: The first obtained data proved the suitability of the developed miniaturized enzymatic assay for fecal contamination monitoring. It can be used for the detection and indirect quantification of E. coli, without the need for confirmatory steps.  Conclusions: This study suggests that the proposed analytical protocol is suitable for E. coli monitoring in seawater, and provides in a short time (i.e. 2 hours from sampling) results which are in agreement with the standard culture counts. Brief summary: The results obtained with the developed IBDG protocol encourage its use for environmental quality assessment. Any potential implications: The possibility to obtain near "real-time" data on the occurrence and distribution of anthropogenic inputs makes this method a simple and quick tool for early warning detection of marine fecal pollution.